1990
DOI: 10.1111/j.1365-2141.1990.00082.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Direct activation of platelets by heat is the possible trigger of the coagulopathy of heat stroke

Abstract: Summary The trigger of the coagulopathy that complicates heat stroke is obscure, but direct platelet activation by heat is a possibility we set out to study. Platelet rich plasma (PRP), prepared from blood donors, was incubated at increasing temperatures (38–45°C) and then platelet aggregation was undertaken in response to decreasing low doses of ADP (<2.0 μmol/l). Hyperaggregability was manifested when the incubation temperature reached 43°C and was maximum at 44°C before complete inhibition of responses at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Experiments with ex vivo platelets, however, demonstrate that heat‐induced platelet hyperaggregability (an index of activation) requires incubation temperatures as high as 43°C (Gader et al. ), and it is unlikely that platelets of participants within the current studies were exposed to regional body temperatures higher than 40°C under passive conditions. Alternatively, adrenergic (Tschuor et al.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Experiments with ex vivo platelets, however, demonstrate that heat‐induced platelet hyperaggregability (an index of activation) requires incubation temperatures as high as 43°C (Gader et al. ), and it is unlikely that platelets of participants within the current studies were exposed to regional body temperatures higher than 40°C under passive conditions. Alternatively, adrenergic (Tschuor et al.…”
Section: Discussionmentioning
confidence: 83%
“…An increase in body temperature per se could be considered a mechanism inducing PMV appearance, as an elevation in procoagulant annexin-V + microvesicles has been observed in the circulation of baboons experiencing severe heat stress and heatstroke (rectal temperaturẽ 44°C) (Bouchama et al 2008), and moderate passive heat stress in humans (+1.3°C in core temperature) has been shown to increase procoagulant activity in the blood (Meyer et al 2013). Experiments with ex vivo platelets, however, demonstrate that heat-induced platelet hyperaggregability (an index of activation) requires incubation temperatures as high as 43°C (Gader et al 1990), and it is unlikely that platelets of participants within the current studies were exposed to regional body temperatures higher than 40°C under passive conditions. Alternatively, adrenergic (Tschuor et al 2008) and purinergic (Yegutkin et al 2007) activation of platelets may stimulate PMV production during exercise, but these hypothetical mechanisms also need to be evaluated.…”
Section: Mechanistic Insightsmentioning
confidence: 99%
“…In vitro studies have shown that heat (43-44ºC) directly activates platelet aggregation and causes irreversible hyperaggregation following cooling 19 . Early in heat stroke, widespread activation of coagulation stimulates excess deposition of fibrin in the arterioles and capillaries along with platelet aggregation that leads to microvascular thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6 provides an overview of the extrinsic and intrinsic pathways that stimulate DIC. Heatinduced injury to the vascular endothelium is considered the primary event that initiates coagulation in heat stroke patients and was shown in vitro (43-44°C) to activate platelet aggregation and cause irreversible hyperaggregation that persisted despite cooling [48,53,116,275,416]. Fibrin deposition with platelet aggregation occludes arterioles and capillaries resulting in microvascular thrombosis that often leads to multi-organ system dysfunction [234].…”
Section: Hematologic Disturbances and Coagulopathiesmentioning
confidence: 99%